Development trend and technological challenges of millimeter-wave wireless communication - Shiwen HE; Yongming HUANG; Haiming WANG; Wei HONG (Dianxin kexue)
Facing the bottleneck problem of the scarcity of the traditional spectrum resource and the demand of wireless business that increases explosively,millimeter-wave (mmWave) communication with rich available spectrum resources become a promising way for the next generation broadband wireless cellular communication.However,the features of the large propagation path loss and severe oxygen and water molecules absorb of mmWave bring great challenge to the mmWave communication technology research.After analyzing the propagation properties of mmWave communication,a comprehensive analysis and summary of the research progress and radio front end were given out.Challenges of mmWave communication were profoundly analyzed and the corresponding research direction was put forward.